2005
DOI: 10.3121/cmr.3.4.229
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular Heterotopia: New Insights into Ehlers-Danlos Syndrome

Abstract: Nature often employs similar mechanisms to complete similar tasks, thus the evolution of homologous proteins across various organ systems to perform similar but slightly different functions. In this respect, disorders attributed to specific genetic mutations, while initially thought to be restricted in function and purpose, may provide broad insight into general cellular and molecular mechanisms of development and maintenance. One such example can be seen in the brain malformation, periventricular heterotopia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…It was further proposed that PH may represent a disorder of impaired periventricular intercellular or cell-matrix adhesion and the authors postulated that aortic dilatation and hyperextensible skin observed in EDS-PH may have similar pathological underpinnings. 10 Gó mez-Garre et al 5 reported EDS-PH due to an FLNA mutation (p.Ala128Val), in females in a pedigree presenting with seizures and joint hypermobility, but they reported no cardiovascular involvement except for mitral valve prolapse. Solé et al 7 screened patients presenting with PH for mutations in FLNA and identified 15 carriers out of 32 screened.…”
Section: Discussionmentioning
confidence: 99%
“…It was further proposed that PH may represent a disorder of impaired periventricular intercellular or cell-matrix adhesion and the authors postulated that aortic dilatation and hyperextensible skin observed in EDS-PH may have similar pathological underpinnings. 10 Gó mez-Garre et al 5 reported EDS-PH due to an FLNA mutation (p.Ala128Val), in females in a pedigree presenting with seizures and joint hypermobility, but they reported no cardiovascular involvement except for mitral valve prolapse. Solé et al 7 screened patients presenting with PH for mutations in FLNA and identified 15 carriers out of 32 screened.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55][56] Otherwise, FLNA mutations could decrease the connection of the cells to the extracellular matrix or compromise regulation to the cytoskeleton through the FLNA binding to integrins proteins. 49,57 Furthermore, a relationship between FLNA and collagen can have a role in the mechanism of platelet aggregation; in fact, mutations in the FLNA and in COL3A1 gene (vascular type of EDS) are both known to determine excessive bleeding, probably due to vascular fragility and platelet dysfunction 49,58 ; mutations in FLNA can cause classic bilateral PNH, [59][60][61][62][63][64]32,65 and the inheritance can be X-linked dominant (mutations in the Filamin A gene) or autosomal recessive (mutations in ARFGEF2 gene). 40 This last mutation has been associated to PNH but in patients without EDS.…”
Section: Eds and Periventricular Heterotopiamentioning
confidence: 97%
“…A disruption in the link between the extracellular matrix and cytoskeleton could cause an aberration in cellular migration during development with possible congenital malformations of the vessels and the brain parenchyma, including cortical dysgenesis. 40,48,49 EDS is considered a disorder of the extracellular matrix related with a disruption in glycoproteins, involving collagen or proteoglycans or other extracellular matrix proteins like Tenascin-X. 36,50,51 Cells join to the extracellular matrix by integrins, whose intracellular portion binds to the actin filaments of the cytoskeleton.…”
Section: Eds and Periventricular Heterotopiamentioning
confidence: 99%
“…Our previous experience indicated that mutations of FLNA are found in up to 26% of sporadic patients with classic bilateral PNH 3 and in only 4% of other phenotypic subclasses of PNH, including PNH with Ehlers-Danlos syndrome 24 and unilateral PNH. FLNA cannot be completely ruled out as the causative gene in all patients of this cohort, as mutation in noncoding regions, larger deletions/duplications involving 1 or more exons, and cryptic chromosomal abnormalities involving FLNA might still be present.…”
Section: Discussionmentioning
confidence: 99%